Efficient electrochemical reduction of CO2 into CO promoted by sulfur vacancies. (June 2019) - Qin, Binhao; Li, Yuhang; Wang, Hongjuan; Yang, Guangxing; Cao, Yonghai; Yu, Hao; Zhang, Qiao; Liang, Hong; Peng, Feng
Abstract: Electrochemical conversion of carbon dioxide (CO2 ) into useful chemicals has attracted a lot of attention to store energy and reduce the greenhouse effect. Herein, a new electrocatalyst of carbon nanotubes coated with cadmium sulfide is reported, the faradaic efficiency (FE) of CO2 reduction reaction (CO2 RR) to carbon monoxide (CO) is as high as 95%. We clearly demonstrate that sulfur vacancies (S-vacancies) are in-situ generated on the catalyst surface in CO2 RR, which is evidenced by electron paramagnetic resonance spectra (EPR), in-situ differential electrochemical mass spectrometry (DEMS) and inductively-coupled plasma spectrometer (ICP). With the increase of S-vacancies, the catalytic activity of CO2 RR to CO improve significantly and the charge-transfer resistance decrease. Combined with in-situ infrared absorption spectroscopy and density functional theory calculations, it can be concluded that the formation of S-vacancies changes the electron density of the catalyst surface and decreases the energy barrier for the conversion of COOH ∗ to CO ∗ . Finally, we tried to power electrochemical reduction of CO2 with solar panel under natural light conditions, the energy conversion efficiency on CdS-CNT catalyst from solar energy to CO has been calculated, predicting a hopeful application prospect in the future. Graphical abstract: Image 1 Highlights: A new electrocatalyst of carbon nanotubes coated with cadmium sulfide is reported. The prepared catalyst shows a high activity and selectivity for CO2 reduction to CO. Sulfur vacancy in-situ generated promotes the electrochemical reduction of CO2 to CO. Electrocatalytic mechanism is revealed by in-situ spectra and theory calculations. Electrochemical reduction of CO2 is powered by solar panel under natural light conditions.